An Outbreak of Carbapenem-Resistant Klebsiella pneumoniae in an Intensive Care Unit of a Major Teaching Hospital in Chongqing, China - Zeng, Lingyi; Yang, Chengru; Zhang, Jisheng; Hu, Kewang; Zou, Jingbo; Li, Jie; Wang, Jianmin; Huang, Wan; Yin, Lining; Zhang, Xiaoli (Frontiers in Cellular and Infection Microbiology, 2021)
Background Due to the critical condition and poor immunity of patients, the intensive care unit (ICU) has always been the main hospital source of multidrug-resistant bacteria. In recent years, with the large-scale use of antibiotics, the detection rate and mortality of carbapenem-resistant Klebsiella pneumoniae (CRKP) have gradually increased. This study explores the molecular characteristics and prevalence of CRKP isolated from the ICU ward of a tertiary hospital in China. Methods A total of 51 non-duplicated CRKP samples isolated from the ICU were collected from July 2018–July 2020. The enzyme production of the strains was preliminarily screened by carbapenemase phenotypic test, and drug-resistant and virulence genes were detected by PCR. The transferability of plasmid was verified by conjugation test. The minimal inhibitory concentration (MIC) was determined by microbroth dilution method and genetic diversity was detected by multilocus sequence typing and pulsed-field gel electrophoresis. Results blaKPC-2 was the only carbapenemase detected. The major virulence genes were uge (100%), mrkD (94.1%), kpn (94.1%), and fim-H (72.5%), while wcag, ironB, alls and magA genes were not detected. One sequence type ST1373 strain, hypervirulent K. pneumoniae (hvKP), was detected. CRKP strains were highly resistant to quinolones, cephalosporins, aminoglycosides, and polymyxin, but susceptive to tigecycline and ceftazidime–avibactam. The success rate of conjugation was 12.2%, indicating the horizontal transfer of blaKPC-2. Homology analysis showed that there was a clonal transmission of ST11 CRKP in the ICU of our hospital. Conclusion The present study showed the outbreak and dissemination in ICU were caused by ST11 CRKP, which were KPC-2 producers, and simultaneously, also carried some virulence genes. ST11 CRKP persisted in the ward for a long time and spread among different areas. Due to the widespread dispersal of the transferable blaKPC-2 plasmid, the hospital should promptly adopt effective surveillance and strict infection control strategies to prevent the further spread of CRKP. Ceftazidime–avibactam showed high effectiveness against CRKP and could be used for the treatment of ICU infections.